Herbaceous vegetation for traffic islands - Holmberg, Hanna (2022)
Today many of us spend a big part of our lives in the grey hardscape that dominates our urban environments. There is research pointing towards the health benefits gained from nature as well as the ecological values that vegetation brings to our cities. Despite this a lot of the green spaces or patches within our cities are not being designed in a way that they reach their full potential. There is an over representation of mowed lawns and trees not well suited for the harsh environment. Whereas perennials are often overlooked or neglected altogether. In this thesis the potential benefits of using herbaceous vegetation in the traffic environment is explored. Would it be possible to transform the larger and perhaps smaller traffic islands so that they provide both aesthetic and ecological values by using perennials? Through looking at existing research the topics of how people and plants are affected by the urban environment and how plants can impact people are explored. Further on the potential for using nature as a source for both inspiration and knowledge are looked into. As a way to test the result from the literature study three traffic intersections in Bromma, Stockholm, receive planting design proposals. These involve replacing the mowed lawns with a more diverse herbaceous vegetation. The thought to inspire municipalities and other professionals to embrace the herbaceous vegetation and incorporate it more in our urban environment.